High Pressure Deuterium Passivation of Charge Trapping Layer for Nonvolatile Memory Applications - Jae-Young Sung; Jun-Kyo Jeong; Woon-San Ko; Jun-Ho Byun; Hi-Deok Lee; Ga-Won Lee (Micromachines, 2021)
In this study, the deuterium passivation effect of silicon nitride (Si3N4) on data retention characteristics is investigated in a Metal-Nitride-Oxide-Silicon (MNOS) memory device. To focus on trap passivation in Si3N4 as a charge trapping layer, deuterium (D2) high pressure annealing (HPA) was applied after Si3N4 deposition. Flat band voltage shifts (ΔVFB) in data retention mode were compared by CV measurement after D2 HPA, which shows that the memory window decreases but charge loss in retention mode after program is suppressed. Trap energy distribution based on thermal activated retention model is extracted to compare the trap density of Si3N4. D2 HPA reduces the amount of trap densities in the band gap range of 1.06–1.18 eV. SIMS profiles are used to analyze the D2 profile in Si3N4. The results show that deuterium diffuses into the Si3N4 and exists up to the Si3N4-SiO2 interface region during post-annealing process, which seems to lower the trap density and improve the memory reliability.